Characterising firearm-related databases across Canada: opportunities for data linkage to inform understanding of injury burden and prevention - Karanikas, Aliki; Gomez, David; Raveendran, Tharani; Saunders, Natasha (International Journal of Population Data Science, 2025)
Introduction Firearm injuries are a significant public health issue in Canada, yet the broader consequences, particularly non-fatal injuries, remain under examined in research and policy discussions. These injuries impose long-term physical, psychological, and social burdens on survivors and create substantial economic costs. While firearm-related injury data are collected across health, justice, and policing sectors, the lack of integration between these datasets hampers a comprehensive understanding of the issue. Objectives This study aims to explore opportunities for linking national, provincial, and municipal datasets on firearm-related injuries in Canada, focusing on data from healthcare, legal, and firearm-specific domains. Methods A comprehensive search for publications related to firearms of Medline, Scopus, and Web of Science and grey literature up to February 2025 identified several relevant datasets, including health records, death registries, and crime databases. Results We found that while valuable information exists, the datasets are siloed, limiting the ability to analyse firearm injuries holistically. Gaps in data, such as the psychological impact of firearm injuries and specific details on firearm ownership, further constrain research. Despite these challenges, linking healthcare, justice, and firearm data could offer critical insights into the epidemiology of firearm injuries, their long-term effects, and associated risk factors. Conclusions Overcoming operational constraints related to privacy, data quality, and funding will be essential for advancing this research and informing evidence-based interventions to reduce firearm-related harm. Drawing from successful data integration initiatives in other jurisdictions, such as Sweden and Australia, this study advocates for the development of a cross-sectoral data linkage strategy to enhance firearm injury prevention and policy development in Canada.